Keumamah Processing Strategy as an Alternative Family Protein Source Stunting Prevention Effort - Sukma Elida; Itza Mulyani; Arif Iskandar (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2022)
Stunting is one of the essential nutritional problems experienced by toddlers globally, especially in developing countries, including Indonesia. The impact of Stunting is not only in terms of health but also affects the level of intelligence of children. This study aims to find a keumamah product formulation that can be useful for supplementary feeding to prevent Stunting. The research design of this study is the Intact-Group Comparison model with two variables; (1) the experimental group and (2) the control group. To find the result, this research involves two types of test; pre-test and post-test. The pre-test is conducted before the experiment, while the post-test is performed after investigating both sample groups. The content of macronutrients, such as protein, fat, and carbohydrates, is higher in keumamah (Wooden fish), made from fresh fish with an oven drying process. The Keumamah made from fresh fish with the drying method using an oven is also more hygienic than those made from less fresh fish with the traditional drying process (Sun-drying). Keumamah dried in an oven is better than Keumamah dried with the conventional drying process (Sun-drying).